Manajemen Mutu Pendidikan Islam Pada Masa Pandemi Covid 19 Di Sma NU Bancar - Imam Sutondo; Barnoto , (Chalim Journal of Teaching and Learning (CJoTL), 2022)
This study aims to describe, explain and know the quality management of learning planning, quality management of learning implementation, quality management of learning evaluation, and quality management of follow-up evaluation of online learning in SMP Techno Insan Kamil.Technique used as data collecting tool in this research is interview technique, observation, and documentation. This research was conducted on Islamic Education Teachers (PAI) and Principal in SMA NU Bancar. The data analysis technique in this research is using data reduction techniques, data display and draw conclusions. To test the validity of the data using triangulation. The result of this research shows that Quality Management of Learning Planning at SMP Techno Insan Kamil. has been done well, that is planning, organizing, processing time, media selection and method as stated in RPP and Syllabus. The Quality Management of Online Learning in SMA NU Bancar. has been implemented well, where the teacher performs opening activities, core activities, and closing activities. Furthermore, Quality Management of Learning Evaluation in SMA NU Bancar. has been applied effectively ie the teacher performs evaluation planning based on Competence Standards and Basic Competence, in the assessment is done by arranged and based on the assessment indicators and the follow-up of Remidial and Enrichment on the students. As well as Quality Control of Learning Supervision has also been well implemented in SMA NU Bancar. ie supervision of the implementation of learning done by the principal directly.